Effect of Neutralizing Transforming Growth Factor β1 on the Immune Response against Mycobacterium tuberculosis in Guinea Pigs - Allen, Shannon Sedberry (American Society for Microbiology, 2004)
Transforming growth factor β (TGF-β) is a cytokine which has been shown to suppress the antimycobacterial immune responses of humans and experimental animals. In this study, the contributions of TGF-β to cytokine production in vivo were investigated by using the established guinea pig model of tuberculous pleurisy. Mycobacterium bovis BCG-vaccinated guinea pigs were injected intrapleurally with heat-killed virulent Mycobacterium tuberculosis. Eight days following induction of an antigen-specific pleural effusion, guinea pigs were injected intrapleurally with anti-TGF-β1 or isotype control antibody. The following day, pleural exudates were removed, and the fluid volume and characteristics of the infiltrating cells were determined. Pleural fluid was analyzed for total interferon (IFN) and tumor necrosis factor (TNF) protein levels by using appropriate bioassays. RNA from pleural effusion cells was examined to determine TGF-β1, TNF-α, IFN-γ, and interleukin-8 mRNA levels by using real-time PCR. Proliferative responses of pleural effusion lymphocytes were examined in response to concanavalin A and purified protein derivative (PPD) in vitro. Treatment with anti-TGF-β1 resulted in decreased pleural fluid volume and decreased cell numbers in the pleural space along with an increased percentage of lymphocytes and a decreased percentage of neutrophils. The bioactive TNF protein levels in pleural fluid were increased in guinea pigs treated with anti-TGF-β1, while the bioactive IFN protein concentrations were not altered. Expression of TGF-β1 and TNF-α mRNA was significantly increased following TGF-β1 neutralization. Finally, PPD-induced proliferative responses of pleural cells from anti-TGF-β1-treated animals were significantly enhanced. Thus, TGF-β1 may be involved in the resolution of this local, mycobacterial antigen-specific inflammatory response.